Life [videorecording (DVD)] - Gyllenhaal, Jake, 1980-; Ferguson, Rebecca, 1983-; Reynolds, Ryan (Sony Pictures Home Entertainment, 2017)
The six-member crew of the International Space Station is on the cutting edge of one of the most important discoveries in human history: the first evidence of extraterrestrial life on Mars. As the crew begins to conduct research, their methods end up having unintended consequences and the life form proves more intelligent than anyone ever expected.